Photocatalytic Decolourization of Direct Yellow 9 on Titanium and Zinc Oxides - Elżbieta Regulska; Diana Małgorzata Bruś; Joanna Karpińska (International Journal of Photoenergy)
The photodecolourization of Direct Yellow 9, a member of the group of azo dyes which are commonly used in the various branches of the industry, was investigated. The photostability of this dye was not previously examined. Photocatalytic degradation method was evaluated. Solar simulated light (E=500 W/m2), titanium dioxide, and zinc oxide were used as irradiation source and photocatalysts, respectively. Kinetic studies were performed on a basis of a spectrophotometric method. Degradation efficiency was assessed by applying high performance liquid chromatography. Disappearance of a dye from titanium dioxide and zinc oxide surfaces after degradation was confirmed by thermogravimetry and Raman microscopy. Direct Yellow 9 was found to undergo the photodegradation with approximately two times higher efficiency when zinc oxide was applied in comparison with titanium dioxide. A simple and promising way to apply the photocatalytic removal of Direct Yellow 9 in titanium dioxide and zinc oxide suspensions was presented.